2021
DOI: 10.3758/s13414-021-02406-x
|View full text |Cite|
|
Sign up to set email alerts
|

Salience matters: Distractors may, or may not, speed target-absent searches

Abstract: Attention is often captured by irrelevant but salient changes in the environment and usually results in slowed search speeds and increased errors during a typical visual search task. Nonetheless, a recent study conducted by Moher (2020) found that the effect of a highly salient distractor on visual search depended on whether or not a target was also present in the display. While the distractor slowed search and increased errors for target-present trials, it speeded search for targetabsent trials. Here, we aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
(52 reference statements)
5
11
0
Order By: Relevance
“…The search accuracy rates across different conditions are shown in Table 1. A two-way ANOVA over the search accuracy data showed that there was a significant main effect of target, F(1, 19) = 16.170, p = .001, η p 2 = .460, in that accuracy rates were lower overall when the target was present (M = 98.1%) than when the target was absent (M = 99.3%), consistent with the findings of previous research (e.g., Chun & Wolfe, 1996;Lawrence & Pratt, 2022;Moher, 2020;Treisman & Gelade, 1980). The main effect of distractor was just significant, F(1, 19) = 5.381, p = .032, η p 2 = .221, with lower accuracy rates on matching-distractor trials (M = 98.4%) than on mismatching-distractor trials (M = 98.9%).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The search accuracy rates across different conditions are shown in Table 1. A two-way ANOVA over the search accuracy data showed that there was a significant main effect of target, F(1, 19) = 16.170, p = .001, η p 2 = .460, in that accuracy rates were lower overall when the target was present (M = 98.1%) than when the target was absent (M = 99.3%), consistent with the findings of previous research (e.g., Chun & Wolfe, 1996;Lawrence & Pratt, 2022;Moher, 2020;Treisman & Gelade, 1980). The main effect of distractor was just significant, F(1, 19) = 5.381, p = .032, η p 2 = .221, with lower accuracy rates on matching-distractor trials (M = 98.4%) than on mismatching-distractor trials (M = 98.9%).…”
Section: Resultssupporting
confidence: 88%
“…It is therefore conceivable that the currently observed distractor effect on search termination is exclusively generated through active maintenance of information in visual working memory. The present results extend previous work, which has established that the presence of a physically salient distractor causes search termination to occur earlier (Moher, 2020; but see Lawrence & Pratt, 2022). Here, we further corroborate distractor effects on quitting behavior in visual search by demonstrating that the presence of a distractor matching the content of visual working memory causes search termination to occur later.…”
Section: Discussionsupporting
confidence: 91%
“…These effects were consistent across age and did not depend on the child explicitly recognizing their caregiver during the task. These results are consistent with recent findings demonstrating that the presence of highly salient distractors makes adults more likely to stop searching early (Lawrence & Pratt, 2022; Moher, 2020). These error data suggest that caregiver faces, more so than stranger faces, were highly salient distractors that may have led participants to abort their search.…”
Section: Discussionsupporting
confidence: 93%
“…Future work could also explore the impact of target presence on the processing of single and multiple salient distractors. Previous work has shown that the presence of a singleton distractor impacts search differently when a target is present or absent (Lawrence & Pratt, 2022; Moher, 2020), and we previously observed overall enhanced P D components when a target was present in the same search display (Drisdelle & Eimer, 2021). Although there were no interactions between target presence and distractor suppression effects in the present work, it will be important to further investigate the impact of this factor on the processing of salient distractors.…”
Section: Discussionsupporting
confidence: 51%